Girassol fertirrigado com doses de potássio em duas safras agrícolas nos semiárido brasileiro - Santos, Allysson Pereira dos (2018)
The sunflower (Helianthus annus L.) has been gaining prominence in the world market, because it presents high capacity in oil production, with excellent quality in its achenes. Due to the great nutritional requirement of this crop, especially the potassium nutrient, its supply through fertilization via fertigation, the increase in precision and the use of split doses favor its absorption by the plant, for maximum yield in productive and economic efficiency. In this sense, experiments were conducted in two agricultural crops in 2016 and 2017 to evaluate the efficient use of fertirrigated potassium doses in sunflower cultivars in the northeastern semiarid region, Mossoró-RN. The experimental design was in randomized blocks, in subdivided plots, with four replications. In the plots, five potassium doses were evaluated: 0, 30, 60, 90 and 120 kg ha-1 of K2O, and in the subplots, four sunflower cultivars: Aguará 6, Altis 99, Multissol and BRS 122. The evaluated production characteristics were: Potassium content in the diagnostic leaf (TKF), mass of a thousand achenes (MMA), yield of achenes (PA), oil content (TO) and oil productivity (PO). The potassium doses increased in the productive results of the agricultural crops, the crop 2 obtained a better result in comparison with the harvest 1. The maximum yields of achenes were 77.7; 80.2; 73.7 and 79.9 kg ha-1 of K2O in crop 1, and 65.9; 69.5; 70.4 and 69.1 kg ha-1 of K2O in crop 2, respectively, for the cultivars Aguará 6, Altis 99, Multissol and BRS 122. The cultivars Aguará 6 and Altis 99 obtained the highest yields of achenes and oil in the two agricultural crops. From the economic study, it was verified that the doses of potassium influenced in all the economic variables, through the results obtained between the two agricultural crops. The highest net income was obtained by cultivars Aguará 6 and Altis 99 in the amount of R$ 3,416.09 and R$ 2,462.07 in crop 1, and R$ 2,287.01 and R$ 1,861.99 in crop 2. Variables of nutritional efficiency of the sunflower fertirrigado with potassium, the cultivars showed variations of behavior in the evaluated efficiencies as a function of potassium doses. The doses of 90 and 120 kg ha-1 of K2O, as well as the greater accumulation in the plant, caused a reduction in the value of nutritional efficiencies, and the cultivar Aguará 6 obtained the best result with the dose of 60 kg ha-1 of K2O, showing enough efficiency in the use and accumulation of this nutrient in the two agricultural crops